2017
DOI: 10.1053/j.gastro.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Factors Interact With Tobacco Smoke to Modify Risk for Inflammatory Bowel Disease in Humans and Mice

Abstract: BACKGROUND & AIMS The role of tobacco smoke in the etiology of inflammatory bowel disease (IBD) is unclear. We investigated interactions between genes and smoking (gene–smoking interactions) that affect risk for Crohn’s disease (CD) and ulcerative colitis (UC) in a case-only study of patients and in mouse models of IBD. METHODS We used 55 immunochip-wide data sets that included 19,735 IBD cases (10,856 CD cases and 8879 UC cases) of known smoking status. We performed 3 meta-analyses each for CD, UC, and IBD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 46 publications
(66 reference statements)
3
51
0
Order By: Relevance
“…A gene-smoking interaction study found that smoking interacted with, for example, NOD2 and IL10 , and seven loci were found to interact differentially with CD and UC (Yadav et al, accepted [66]).…”
Section: Defining Study Hypotheses To Be Evaluatedmentioning
confidence: 99%
“…A gene-smoking interaction study found that smoking interacted with, for example, NOD2 and IL10 , and seven loci were found to interact differentially with CD and UC (Yadav et al, accepted [66]).…”
Section: Defining Study Hypotheses To Be Evaluatedmentioning
confidence: 99%
“…IBD has a high incidence that affects millions of people globally and the prevalence increases annually . There are many factors thought to lead to the development of colitis, such as age, environment, gender, genetics, and diet . Recent advances in next‐generation sequencing technology have shown that IBD may also result from alterations in the composition and function of gut microbiota, referred to as dysbiosis.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the risk of UC was significantly increased with former smoking and the low frequency of HLA‐DRB1*15:02 in controls (< 5%), initiating smoking for reducing the risk of UC should not be recommended. Previous studies evaluating HLA–smoking interactions associated with UC in a Caucasian population reported that only the HLA‐DRB3*91:01 allele showed a possible interaction with smoking . However, because of the absence of DRB3 alleles in the Korean panel, we were unable to evaluate the interaction of smoking with HLA‐DRB3.…”
Section: Discussionmentioning
confidence: 86%